MODIFIKASI STRATEGI KREATIF PENGAMEN TUNANETRA DALAM MEMBANGUN INTERAKSI SOSIAL: STUDI KASUS : PENGAMEN TUNANETRA DI JALAN MALIOBORO YOGYAKARTA - Anantha Angriany Sitio (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
The purpose of this study is to identify changes in creative tactics created by blind people in performing busking. Changes in the rules in the arrangement of the Malioboro tourist location by the Yogyakarta government require blind buskers to change their busking strategy, which used to be walking along Malioboro Street (busking by moving around) to having to settle at a point that has been determined by the Yogyakarta government. In practice, the regulation makes changes for blind buskers along Malioboro Street. The changes are related to the strategies that must be changed, which were previously nomadic but must change to being settled. The purpose of this study is to examine the modification of creative tactics built by blind buskers to achieve success in their busking performances. Observation and interview are a combination of data collection methods in this study. The selection of informants with the purposive sampling method. The results of this study indicate that the busking strategy with the nomadic method is different from non-nomadic busking. Creative tactics occur in various elements such as speakers, volume, sharing tasks, direction of face, and pauses.